S-oxiracetam ameliorates ischemic stroke induced neuronal apoptosis through up-regulating α7 nAChR and PI3K / Akt / GSK3β signal pathway in rats. (May 2018) - Fan, Wenxiang; Li, Xiang; Huang, Liangliang; He, Shucheng; Xie, Zhicheng; Fu, Yuxin; Fang, Weirong; Li, Yunman
Abstract: Ischemic stroke, the main reason for severe disabilities in the world, is associated with a high incidence of sensorimotor and cognitive dysfunction. In this study, we use the middle cerebral artery occlusion/reperfusion (MCAO/R) model in rats and oxygen glucose deprivation/reoxygenation (OGD/R) model in fetal rat primary cortical neurons to investigate whether and how S-oxiracetam (S-ORC) protect brain injury from ischemic stroke. The results revealed that S-ORC reduced brain infarct size and lessened neurological dysfunction after stroke. Further study demonstrated that S-ORC diminished TUNEL positive cells, increased cell viability, decreased LDH activity, and inhibited cell apoptotic rate. Furthermore, S-ORC inhibited neuronal apoptosis by activating the PI3K/Akt/GSK3β signaling pathway via α7 nAChR, which was evidenced by α7 nAChR siRNA. In conclusion, our findings strongly suggest that S-ORC could be used as an effective neuroprotective agent for ischemic stroke due to its effect in preventing neuronal apoptosis. Highlights: The effects of S-ORC on ischemic stroke. The possible mechanism is related to inhibiting apoptosis. The molecular mechanism is via α7 nAChR signal.